Analisa Pengaruh Aplikasi Hafalan Al-Quran Juz 30 Berbasis iOS Terhadap Motivasi Pengguna Menggunakan Model MSLQ - Hamidah, Dewi Nurul Hamidah; Rina Yulius (MULTINETICS, 2024)
Indonesia is a country with the largest Muslim population in the world, but the number of Qur'an memorizers in Indonesia is still relatively small. One of the main obstacles faced is the lack of motivation in memorizing the Qur'an. One approach that can help increase motivation in memorizing is an approach through application media, considering the use of gadgets in Indonesia continues to increase, the application media approach is a potential solution. Through the application, the memorization process can become more interactive by utilizing surprising and delightful techniques. This research is limited to Al-Qur'an Juz 30 which is the final part of the Al-Qur'an. In addition to building the Qur'an memorization application, this research also analyzes the effect of the iOS based Juz 30 Qur'an memorization application on user motivation using the Motivated Strategies for Learning Questionnaire (MSLQ) model. The measurement results show that there is an influence between the Al-Qur'an memorization application and user motivation in memorizing. The Al-Qur'an memorization application has an influence of 26.2% on user motivation, while 73.8% of memorization motivation is influenced by other factors outside the study. Thus, it can be concluded that the Al-Qur'an memorization application has an influence on user motivation in memorizing, but there are still other factors that also affect this motivation.